Geographies of exclusion : society and difference in the West - Sibley, David (Routledge, 1995)
Analyses the construction of socio-spatial boundaries seen in gender, colour, sexuality, age, lifestyle and disability, arguing that powerful groups tend to dominate space to create fear of minorities in the home, community and state.